Commodification, casualisation and intensification of work in liberalised European postal markets. (1st October 2008) - Christoph Hermann; Torsten Brandt; Thorsten Schulten
Abstract : This article argues that liberalisation and privatisation of public services have led to a commodification of public sector work and labour relations. Using the example of European postal services it describes the process of liberalisation, privatisation and the resulting changes in company strategies and organisation. It argues that commercialisation has not only changed the nature of service provision, but has also caused a far-reaching intensification and casualisation of employment in the European postal sector.